Mobile Tracking on Patient Progress(m-TOPP) - Dalbouh, Hussain Mohammad Yousef Abu (2009)
Much of the supportive technology developed for use within medical environments is targeted towards computers. In this report we present a study performed to use mobile application for store and follow up patient’s state. With the increasing of hospital demands and challenge doctors and nurses face problems in tracking the conditions of patients. Health-care professionals spend much of their time wandering between patients and offices, while the supportive technology stays stationary. Therefore Mobile Tracking on Patient Progress by using mobile devices is proposed to minimize such challenges and demands, by allowing doctors to track the patient’s conditions more efficiently and easily. The design of the prototype presented in this report reflects how doctors and nurses tracking patient’s condition, and it also allow the doctors to reach the information at any location and at any time. The report concludes that the working environment would be improved by supporting the mobile workers with mobile technology. The main result of this report is a proposition of how to use mobile application to track the patient’s condition and store this information in the data base for efficient access.